Pengaruh Non-Debt Tax Shield Dan Cost Of Financial Distress Terhadap Struktur Modal Pada Perusahaan Sub Sektor Logam Dan Sejenisnya Yang Terdaftar Di Bursa Efek Indonesia (BEI) Tahun 2013-2017 - Muhammad Yusuf; Andika Kurniawan (Neraca : Jurnal Akuntansi Terapan, 2019)
This research aims to provide the influence of non-debt variable tax shield and cost of financial distress affect the capital structure of the company's sub-sector metals and the like listed on the Indonesia Stock Exchange in 2013-2017. The method on this research is a quantitative approach with the type of correlation study. The data collection techniques in this study use secondary data with saturated sampling techniques. The population of this research is a metal sub-sector company and the like listed on the Indonesia Stock Exchange (IDX). The samples in this study were as many as 16 metal sub-sector companies and the like listed on the Indonesia Stock Exchange (IDX). The results showed that both the partial and simultaneous variables of the non-debt tax shield and cost of financial distress had no effect on the capital structure of the metal sub-sector companies and the like listed on the Indonesia Stock Exchange ( IDX). It shows that the T-Test in a non-debt tax shield variable is obtained by the T-calculate result of 1.401 and the value of Sig. T. Acquired by 0, 165 > 0.05, then Ho accepted and H1 rejected which means there is no positive influence on the capital structure and in variable cost of financial distress obtained with the result of T-Calculate of 1.756 and the value of Sig. T. Acquired by 0, 083 > 0.05, then Ho is accepted and H1 is rejected which means there is no positive influence on the capital structure. Then simultaneously F test result in can with a fcalculate value of 2.295 with a level of Sig. 0, 108, because of the value of Sig. F > 0.05, then Ho accepted and H1 rejected. This means that there is no variable influence of non debt tax shield (X1) and cost of financial distress (X2) to the capital structure (Y).